2016
DOI: 10.1089/bio.2015.0022
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Biospecimens at Ambient Temperature: Special Focus on Nucleic Acids and Opportunities for the Biobanking Community

Abstract: Several approaches to the preservation of biological materials at ambient temperature and the relative impact on sample stability and degradation are reviewed, with a focus on nucleic acids. This appraisal is undertaken within the framework of biobank risk, quality management systems, and accreditation, with a view to assessing how best to apply ambient temperature sample storage to ensure stability, reduce costs, improve handling logistics, and increase the efficiency of biobank procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…The mid- and long-term stability of the quality of the samples conserved at low temperature is often difficult to maintain and control, requiring substantial precautions [ 52 , 53 , 54 ]. It is for this reason that several procedures have been developed to maintain the quality and stability at RT of nucleic acids over a long period of time for subsequent use in research [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mid- and long-term stability of the quality of the samples conserved at low temperature is often difficult to maintain and control, requiring substantial precautions [ 52 , 53 , 54 ]. It is for this reason that several procedures have been developed to maintain the quality and stability at RT of nucleic acids over a long period of time for subsequent use in research [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, fitness-for-purpose procedures should be validated and established when a prospective workflow is designed, taking into consideration the general good practices that do allow the most use of samples [2,12]. Independently, other approaches have been reviewed for the conservation of samples at room temperature by biobanks [25]. Before sending of samples to analytical laboratories from the storage facilities, a checkpoint is introduced to guarantee that each aliquot is compliant with the corresponding study or with the necessary volume of sample to thus supplement with additional aliquots.…”
Section: Monitored Storage Of Biological Samples and Distributionmentioning
confidence: 99%
“…It is therefore necessary to improve nucleic acid sample collection to enable highly sensitive NAAT in RLS. It has been shown that extracted RNA stored in dry conditions shows less degradation and more consistent amplification, even when stored at room temperature or elevated temperatures over several weeks [20][21][22][23] . However, nucleic acid extraction from blood prior to shipment to central testing facility can be resource-intensive and impractical for RLS 24 .…”
Section: Introductionmentioning
confidence: 99%